Relationship of Decayed, Missing, Filled, Teeth and Related Indexes of Glomerular Filtration Rate in Various Stages of Chronic Kidney Disease in Adults Residing in ShahediehCity, Yazd Province - Abdolrahim Davari; Alireza Daneshkazemi; Sanaz Abbasi; Farzad Ziaei (Isfahan University of Medical Sciences, 2022)
Oral health problems in patients with chronic renal failure can endanger their systemic health. The aim of this study was to assess the correlation of Decayed, Missing, Filled, Teeth(DMFT) and Glomerular Filtration Rate (GFR).Materials & Methods:In this descriptive-analytical study, using the Shahidieh project conducted on 9000 people from the city of Yazd in 2017 for data collection. The serum creatininelevel, and age, gender and weight of patients were extracted from the questionnaire designed for the Yazd Shahedieh Project after receiving permission. The GFR of each individual was calculated using the Cockcroft Gault formula. For assessment of oral health status, the DMF index of permanent teeth of adults was calculated. The Data analyzed using t-test, ANOVA, Pearson's correlation coefficient, and regression analysis.Results:Weight was not related to the number of carious teeth but was directly related to the number of filled teeth. Weight was also inversely related to the number of missing teeth and DMFT. Serum creatinine was not related to the number of decayed teeth but was directly related to the number of missing teeth and DMFT. Serum creatinine was inversely related to the number of filled teeth. Age was inversely related to the number of decayed and filled teeth, but was directly related to the number of missing teeth and DMFT. GFR is directly related to the number of decayed and filled teeth, but is inversely related to the number of missing teeth and DMFT. GFR and DMFT index had a significant and inverse relationship.Conclusion:According to the present study the lower GFR index and the higher the serum creatinineand the higher the stage of kidney disease, a direct correlation of a high DMFT index was observed.